The emperor's new clothes [videorecording (DVD)] : and more Hans Christian Andersen fairy tales - Westcott, Nadine Bernard; Pinkney, Jerry; Winblad, Bjorn; Sporn, Michael (New Video Group, 2005)
In "The emperor's new clothes," two swindlers create a royal robe from magical cloth for a vain king. In "The ugly duckling," a duckling is teased because of his awkward appearance until he grows into a beautiful swan. In "The swineherd," a spoiled princess scorns the love of an honorable prince until he comes up with a clever way to steal some kisses from her.